The AI Personalization Driven Path To Repurchase Intension in Travel Apps - Ningsih, Nadya Nurlailya; Reken, Feky; Kurniawan, Sabda Aji (Universitas Pahlawan Tuanku Tambusai, 2025)
With the rapid advancement of digital technology, artificial intelligence (AI) plays a vital role in enhancing user experiences in travel applications. This study investigates the influence of AI Personalization (X1) and User Experience (X2) on Repurchase Intention (Y), with E-Satisfaction (Z) as a mediating variable. A total of 380 travel app users in Maluku Province participated via an online survey. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).Results show that AI Personalization and User Experience significantly affect E-Satisfaction, which in turn positively influences Repurchase Intention. E-Satisfaction serves as a key mediator, indicating that satisfied users are more likely to repurchase. Although AI Personalization contributes positively, User Experience has a stronger impact on Repurchase Intention. This suggests that personalization alone is not sufficient to build loyalty. The study highlights the importance for travel app developers to optimize both AI-driven personalization and intuitive user experiences to enhance user satisfaction and encourage repeat purchases. Keywords: AI Personalization, User Experience, E-Satisfaction, Repurchase Intention, Travel Applications, Structural Equation Modeling (SEM), Partial Least Squares (PLS).